PENGARUH INDEPENDENSI PENGAWASAN INTERNAL TERHADAP PENCEGAHAN KORUPSI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI PADA MAHKAMAH AGUNG RI) - Ulfah Apriani; Krissantono Karo Karo; Fatmamita Yuliana; Feliona Astika; Ridwan Ridwan; Darmawan Darmawan; Bustomi Bustomi; Haryono Umar (Prosiding Seminar Nasional Pakar, 2019)
This study aims to obtain empirical evidence of the influence ofIndependence of Internal Oversight on the Prevention of Corruption withOrganizational Commitment as a Moderating Variable (study on theSupreme Court of the Republic of Indonesia). The population in this studywere employees of the Supreme Court of the Republic of Indonesia. Theresearch sample used purposive sampling, namely in the field ofSupervision and Equipment Bureau of Supreme Court of the Republic ofIndonesia. The primary data collection method used is the questionnairemethod. Data was analyzed using SEM PLS. The results of the studyindicate that the independence of Internal Oversight and OrganizationalCommitment has a positive effect on Prevention of Corruption, althoughOrganizational Commitment cannot strengthen the relationship of theinfluence of Independence of internal supervision on CorruptionPrevention.